Arts of eristic, of dialectic and of sophistry as premises of legal discourse development - K. H. Rekoch (Vestnik MGIMO-Universiteta)
Discourse arts of ancient Greece demonstrate in the V century BC division of discourses, and are seen as premises of rhetoric, which marked institutional differentiation of speeches and predestinated legal discourse. The purpose of the following analysis is to show cohesion, coherence and mutual dependence of discourse arts as premises of rhetoric. Sophists confirmed with their example the dichotomies of utterance meanings and though they didn't create eloquence art, they laid a way to rhetoric, laid down foundation for language studying, having isolated it from Logos, and also developed techniques of judicial speeches and legal discourse. Criticizing sophists, using their positive methods, Socrat, Platon and later Aristotle defined, on the basis of syllogism, the direction of evolution of rhetoric not as practical eloquence but mainly as methodology of sciences and arts.